Drug screening platform using human induced pluripotent stem cell‐derived atrial cardiomyocytes and optical mapping. (14th September 2020) - Gunawan, Marvin G.; Sangha, Sarabjit S.; Shafaattalab, Sanam; Lin, Eric; Heims‐Waldron, Danielle A.; Bezzerides, Vassilios J.; Laksman, Zachary; Tibbits, Glen F.
Abstract: Current drug development efforts for the treatment of atrial fibrillation are hampered by the fact that many preclinical models have been unsuccessful in reproducing human cardiac physiology and its response to medications. In this study, we demonstrated an approach using human induced pluripotent stem cell‐derived atrial and ventricular cardiomyocytes (hiPSC‐aCMs and hiPSC‐vCMs, respectively) coupled with a sophisticated optical mapping system for drug screening of atrial‐selective compounds in vitro. We optimized differentiation of hiPSC‐aCMs by modulating the WNT and retinoid signaling pathways. Characterization of the transcriptome and proteome revealed that retinoic acid pushes the differentiation process into the atrial lineage and generated hiPSC‐aCMs. Functional characterization using optical mapping showed that hiPSC‐aCMs have shorter action potential durations and faster Ca 2+ handling dynamics compared with hiPSC‐vCMs. Furthermore, pharmacological investigation of hiPSC‐aCMs captured atrial‐selective effects by displaying greater sensitivity to atrial‐selective compounds 4‐aminopyridine, AVE0118, UCL1684, and vernakalant when compared with hiPSC‐vCMs. These results established that a model system incorporating hiPSC‐aCMs combined with optical mapping is well‐suited for preclinical drug screening of novel and targeted atrial selective compounds. Abstract : Chamber‐specific differentiation of hiPSC‐derived cardiomyocytes allowed for the development of an atrial cardiomyocyte‐based drug screening platform. In‐depth characterization of hiPSC‐derived atrial and ventricular cardiomyocytes revealed chamber‐specific phenotypes in molecular signatures and functional profiles. Drug screening with high‐content optical mapping system captured atrial‐selective pharmacology which demonstrated the utility of hiPSC‐derived atrial cardiomyocytes as an in vitro drug screening model.